Understanding Religion and Science: Introducing the Debate by Michael Horace Barnes. Continuum, 2010. 320pp., pb. £70. ISBN-13: 9781441118165. (28th September 2017) - Brierley, Peter
Abstract : Understanding Religion and Science: Introducing the Debate by Michael Horace Barnes. Continuum, 2010. 320pp., pb. £70. ISBN-13: 9781441118165.